Toxic epidermal necrolysis-like rash of lupus: A dermatologist's dilemma - Brahmita Monga; Sangita Ghosh; V K Jain (Wolters Kluwer Medknow Publications, 2014)
For most dermatologists, the challenge posed by toxic epidermal necrolysis (TEN) lies not in its diagnosis, but in pulling the patient out of this life-threatening condition. However, when a patient presents with a TEN-like picture in the background of lupus erythematosus (LE), it becomes difficult to decide whether the eruption is drug induced or a manifestation of lupus itself.